The Evolution of Advertising: Transition from Traditional Media to Data-Driven Personalization, Automation, and Socially Responsible Campaigns in the Digital Age - Kumar, Sandeep (Journal of Global Economy, Business and Finance, 2025)
Advertising has evolved dramatically, moving from traditional media to a dynamic, data - driven digital landscape. This paper explores the shift from print and broadcast ads to the rise of digital platforms that offer precise targeting and real - time performance analytics. Key trends such as personalization, influencer marketing, video content, and programmatic advertising are shaping the future of the industry. Additionally, the growing emphasis on social responsibility and brand purpose reflects changing consumer expectations. Alongside these opportunities, challenges like ad fatigue, privacy concerns, and ethical practices present new hurdles for advertisers. This paper discusses the evolution, current trends, and the future trajectory of advertising in the digital age.